1998
DOI: 10.1086/302022
|View full text |Cite
|
Sign up to set email alerts
|

Dihydropyrimidinase Deficiency: Structural Organization, Chromosomal Localization, and Mutation Analysis of the Human Dihydropyrimidinase Gene

Abstract: Dihydropyrimidinase (DHP) deficiency (MIM 222748) is characterized by dihydropyrimidinuria and is associated with a variable clinical phenotype. This disease might be associated with a risk of 5-fluorouracil toxicity, although no cases have been reported. We present here both the molecular characterization of the human DHP gene and, for the first time, the mutations causing DHP deficiency. The human DHP gene spans >80 kb and consists of 10 exons. It has been assigned to 8q22, by FISH. We performed mutation ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 32 publications
0
45
0
1
Order By: Relevance
“…Missense mutation G883A in exon 5 has been associated with severe 5-FU toxicity. 58 This mutation has been shown to result in mutant DHP enzyme without residual activity.…”
Section: -Fluorouracilmentioning
confidence: 99%
“…Missense mutation G883A in exon 5 has been associated with severe 5-FU toxicity. 58 This mutation has been shown to result in mutant DHP enzyme without residual activity.…”
Section: -Fluorouracilmentioning
confidence: 99%
“…However, some of the control cats possessed the deletion homozygously or heterozygously, suggesting it is a polymorphism. The p.G435R (c.1303G>A) mutation was previously reported in an asymptomatic human patient with DHPuria, although it was found to be compound heterozygous with the p.Q334R mutation (Hamajima et al 1998). Expression analysis of the human p.G435R mutation in COS-7 cells revealed that it exhibits severely reduced enzymatic activity, demonstrating that p.G435R is a DHP deficiency-causing mutation.…”
Section: Discussionmentioning
confidence: 85%
“…The scientific reason why 5-FU is severely toxic to cats has yet to be clarified, but it may be due to a lower catabolic rate in the breakdown pathway for pyrimidine bases than other species. Therefore, without any medication such as 5-FU, the affected cat is symptomatic due to the p.G435R mutation, which is less deleterious and does not cause a symptomatic DHP deficiency in humans (Hamajima et al 1998). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The human DHP gene, DPYS, has been mapped to chromosome 8q22 by fluorescence in-situ hybridisation, and consists of 10 exons spanning more than 80 kb in the human genome. 2 Dihydropyrimidinase deficiency (MIM 222748) is an autosomal recessive inborn error of pyrimidine metabolism characterised by the presence of dihydropyrimidinuria. The first case of DHP deficiency was first reported by Duran et al 3 The patient was a Turkish male infant presenting with convulsion at 8 weeks after birth; at age 19 months the child appeared to be normal.…”
Section: Introductionmentioning
confidence: 99%